2005
DOI: 10.1002/ijc.20937
|View full text |Cite
|
Sign up to set email alerts
|

Toenail selenium and risk of hepatocellular carcinoma mortality in Haimen City, China

Abstract: Selenium (Se) is an essential trace mineral with known anticarcinogenic properties in humans. However, few studies have examined the association between Se nutrient status and risk of liver cancer. We conducted a nested case-control study comparing the Se content in toenail clippings of 166 individuals (154 men, 12 women) with hepatocellular carcinoma (HCC) to 394 healthy controls (360 men, 34 women) in Haimen City, China, where HCC is a leading cause of mortality. Toenail Se concentration was measured by indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 36 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…It has been demonstrated that various forms of selenium inhibit the initiation phase of carcinogenesis. 17 Recent observations have indicated that the selenium level may interact with alcohol drinking 43 and may be associated with the extent of DNA damage. 44 Based on those observations, we have tested hypotheses that dietary selenium intake may interact with ALDH2, an alcohol metabolic gene, and XRCC1, a DNA repair gene, on the risk of ESCC, although the biologic mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that various forms of selenium inhibit the initiation phase of carcinogenesis. 17 Recent observations have indicated that the selenium level may interact with alcohol drinking 43 and may be associated with the extent of DNA damage. 44 Based on those observations, we have tested hypotheses that dietary selenium intake may interact with ALDH2, an alcohol metabolic gene, and XRCC1, a DNA repair gene, on the risk of ESCC, although the biologic mechanisms remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These epidemiology studies have generated both positive and negative results, but do provide substantial support for the hypothesis that Se compounds have cancer preventive activity (Combs, 2005). In recent years, numerous investigators have reported inverse associations between Se biomarkers (toenail Se or serum Se levels) and the risk of neoplasia in several sites, including the prostate (van den Brandt et al, 2003, Vogt et al, 2003, Li et al, 2004, esophagus and gastric cardia (Wei et al, 2004), liver (Sakoda et al, 2005), colon (Ghadirian et al, 2000;Jacobs et al, 2004;Peters et al, 2006), lung (van den Brandt et al, 1993, Zhuo et al, 2004, skin (Burke et al, 1992), and urinary bladder (Zeegers et al, 2002). It should be noted, however, other studies have found no association between Se status and the risk of cancer of the breast (Dorgan et al, 1998;Ghadirian et al, 2000;Männistö et al, 2000), prostate (Ghadirian et al, 2000;Allen et al, 2004), ovary (Pan et al, 2004), non-cardiac stomach (Wei et al, 2004), urinary bladder (Michaud et al, 2002), or lung (Mahabir et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to chronic HBV infection (2), several other environmental and nutritional cofactors may modify or contribute to risk of liver disease and hepatocarcinogenesis (3,4). One such factor may be folate, a water-soluble B vitamin naturally occurring in several foods.…”
Section: Introductionmentioning
confidence: 99%